2015
DOI: 10.1093/ejcts/ezv404
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after treatment of pulmonary atresia with ventricular septal defect: nationwide study of 109 patients born in 1970–2007

Abstract: These findings show that achievement of repair and initial size of true central pulmonary arteries affect survival of patients with PA + VSD. Although the overall survival of patients with MAPCAs showed no difference compared with simple PA + VSD patients, they had a higher risk of remaining palliated. However, palliative surgery may have a role in treatment of PA + VSD because the size of pulmonary arteries increased after placement of systemic-pulmonary artery shunt. In addition, subtotal repair by a RV-pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
5
15
1
1
Order By: Relevance
“…When grouping the patients into those with PA‐VSD only and those with MAPCAs we found a similar distribution, that is 59% and 41%, respectively. This is in agreement with a study by Kaskinen et al 2 who reported the long‐term outcome in patients with PA‐VSD born in Finland 1970–2007. In patients with both PA‐VSD and MAPCAs (Group 2), four (13.8%) lacked central pulmonary arteries (Figure 1), well in line with previous reports 1,19 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When grouping the patients into those with PA‐VSD only and those with MAPCAs we found a similar distribution, that is 59% and 41%, respectively. This is in agreement with a study by Kaskinen et al 2 who reported the long‐term outcome in patients with PA‐VSD born in Finland 1970–2007. In patients with both PA‐VSD and MAPCAs (Group 2), four (13.8%) lacked central pulmonary arteries (Figure 1), well in line with previous reports 1,19 …”
Section: Discussionsupporting
confidence: 93%
“…The significantly earlier clinical presentation in our patients with PA‐VSD where the pulmonary blood flow was solely dependent on ductal flow, compared to those with MAPCA connections, was clear in our study. This has been described in some other reports, 20 while others, surprisingly, have not found such a difference, 2 in spite of studying a rather large and population‐based cohort. In the present study, all the patients diagnosed during the last five years of the study period were identified prenatally, reflecting the development of foetal cardiology in Sweden in recent years.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, the treatment for those patients remains challenging and highly dependent on the size, distribution, and growth of the native pulmonary arteries and the existence of MAPCAs. Several institutions have reported that patients with MAPCAs showed a lower repair rate, a higher risk of remaining palliate, and higher mortality . The complexity and uncertain outcome in patients with MAPCAs were the main reasons parents chose termination.…”
Section: Discussionmentioning
confidence: 99%
“…MAPCAs showed a lower repair rate, 21,22 a higher risk of remaining palliate, 21,22 and higher mortality. 22,23 The complexity and uncertain outcome in patients with MAPCAs were the main reasons parents chose termination.…”
Section: Mapcas Several Institutions Have Reported That Patients Withmentioning
confidence: 93%